2020
DOI: 10.1002/anie.202013014
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Transition‐Metal Hydroxide Cover Layer for Enhancing Photoelectrochemical Water Oxidation

Abstract: Depositing a transition‐metal hydroxide (TMH) layer on a photoanode has been demonstrated to enhance photoelectrochemical (PEC) water oxidation. However, the controversial understanding for the improvement origin remains a key challenge to unlock the PEC performance. Herein, by taking BiVO4/iron‐nickel hydroxide (BVO/FxN4−x‐H) as a prototype, we decoupled the PEC process into two processes including charge transfer and surface catalytic reaction. The kinetic information at the BVO/FxN4−x‐H and FxN4−x‐H/electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 44 publications
3
39
0
1
Order By: Relevance
“…Open Generally, loading an OEC catalyst on a photoanode should result in an increase in water oxidation rates. 16,20,43 However, k trans of bare BiVO 4 appeared higher than that of NiFeV/B-BiVO 4 to some degree at most potentials (Fig. 4d).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 90%
See 2 more Smart Citations
“…Open Generally, loading an OEC catalyst on a photoanode should result in an increase in water oxidation rates. 16,20,43 However, k trans of bare BiVO 4 appeared higher than that of NiFeV/B-BiVO 4 to some degree at most potentials (Fig. 4d).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 90%
“…The photovoltage of a photoanode arises from splitting of electron and hole quasi-Fermi level under steady-state light illumination, which acts as a driving force for injecting the photogenerated holes into the electrolyte for OER. 65,67 According to several previous works, 30,43,49,62,68 the simple integration of OECs on the surface of photoanodes could enlarge the difference in photovoltage between the dark and light conditions, resulting in greater band bending. 44 Smith and co-workers also reported that the photocharged BiVO 4 photoanodes in a borate buffer solution obtained a favorable band bending, which is responsible for the strong suppression of surface recombination.…”
Section: S7 †)mentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the atomic nature of reactive sites and surface traps is a key enabling step towards optimizing chemical conversion at semiconductor-liquid junctions. [1][2][3] The recent development of operando analysis tools has provided deep insights into the operation of specific semiconductor electrodes for solar-driven H 2 production via water splitting. [4][5][6][7] However, each material brings a unique atomic and electronic structure that requires the development of specific analysis tools and interpretation.…”
mentioning
confidence: 99%
“…Das Verständnis der atomaren Natur reaktiver Zentren und Oberflächenfallen ist ein wichtiger Schritt zur Optimierung der chemischen Umwandlung an Halbleiter-Flüssigkeit-Grenzflächen. [1][2][3] Die jüngste Entwicklung von Operando-Analysetools hat tiefe Einblicke in den Betrieb spezifischer Halbleiterelektroden für die solarbetriebene H 2 -Produktion durch Wasserspaltung ermçglicht. [4][5][6][7] Jedes Material bringt jedoch eine einzigartige atomare und elektronische Struktur mit sich, die die Entwicklung spezifischer Analysewerkzeuge und Interpretation erfordert.…”
unclassified